The Belt and Road Initiative: An Opportunity for Spain - Ríos, Xulio (Sinología hispánica. China Studies Review, 2018)
"The Belt and Road" initiative is the most ambitious international project promoted by the current Chinese leadership. They have weighed internal and external variables in order to launch it. The project covers countries that represent 70% of the world’s population and produce 55% of the global GDP. Spain is part of the initiative, in both versions, by sea and by land. Spain’s involvement in the Silk Road initiative must be essential for the turning point that requires the new time of bilateral relations, which is called to overcome the current apathy. Being sidelined will dangerously worsen the peripheral position that Spain already has within China’s relations with Europe.